Transurethral resection of bladder tumor: A systematic review of simulator-based training courses and curricula - Panagiotis Kallidonis; Angelis Peteinaris; Gernot Ortner; Kostantinos Pagonis; Costantinos Adamou; Athanasios Vagionis; Evangelos Liatsikos; Bhaskar Somani; Theodoros Tokas (Asian Journal of Urology)
Objective: Transurethral resection of bladder tumor is one of the most common everyday urological procedures. This kind of surgery demands a set of skills that need training and experience. In this review, we aimed to investigate the current literature to find out if simulators, phantoms, and other training models could be used as a tool for teaching urologists. Methods: A systematic review was performed according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses statement and the recommendations of the European Association of Urology guidelines for conducting systematic reviews. Fifteen out of 932 studies met our inclusion criteria and are presented in the current review. Results: The UroTrainer (Karl Storz GmbH, Tuttlingen, Germany), a virtual reality training simulator, achieved positive feedback and an excellent face and construct validity by the participants. The inspection of bladder mucosa, blood loss, tumor resection, and procedural time was improved after the training, especially for inexperienced urologists and medical students. The construct validity of UroSim® (VirtaMed, Zurich, Switzerland) was established. SIMBLA simulator (Samed GmbH, Dresden, Germany) was found to be a realistic and useful tool by experts and urologists with intermediate experience. The test objective competency model based on SIMBLA simulator could be used for evaluating urologists. The porcine model of the Asian Urological Surgery Training and Education Group also received positive feedback by the participants that tried it. The Simulation and Technology Enhanced Learning Initiative Project had an extraordinary face and content validity, and 60% of participants would like to use the simulators in the future. The 5-day multimodal training curriculum “Boot Camp” in the United Kingdom achieved an increase of the level of confidence of the participants that lasted months after the project. Conclusion: Simulators and courses or curricula based on a simulator training could be a valuable learning tool for any surgeon, and there is no doubt that they should be a part of every urologist's technical education.